A strikingly polychromatic new species of Gonatodes (Squamata: Sphaerodactylidae) from northern Venezuela - Rivero-Blanco, Carlos; Schargel, Walter E. (Zootaxa, 2012)
We describe a new species of diurnal gecko, Gonatodes rozei sp. nov., from tropical and premontane humid forests ofnorth central Venezuela. The new species can be distinguished from other congeners by a combination of large size, sub-caudal pattern B (1’1’1’’), three or four lateral scale rows on the digits, males with blue iris, scalation of the gular area,and aspects of color pattern in males and females. The new species is strongly sexually dichromatic and up to four different color morphs are observed in males.